Effect of Field Trials on Northern Bobwhite Survival and Hunt Quality on Dixie Plantation - D. Clay Sisson; Theron M. Terhune II (National Quail Symposium Proceedings, 2017)
The potential negative effects of horseback field trials on survival and post trial hunting quality of northern bobwhites (Colinus virginianus) have long been debated. Recent acquisition of Dixie Plantation (3,650 ha) by Tall Timbers Research Station provided a unique opportunity to evaluate this interaction as Dixie has been home to the Continental Field Trial since 1937. We monitored radio-tagged bobwhites annually (n = 183; ~20 coveys during fall/winter) on a core study area (640 ha) upon which a portion of the field trial was conducted during January 2015 & 2016. We estimated Kaplan-Meier survival of radio-tagged bobwhites on Dixie before, during, and after the field trial event as well as compared seasonal survival to bobwhite (N = 387) on nearby Tall Timbers Research Station (1,570 ha) during the same time period. Additionally, we recorded the number of coveys seen, coveys pointed, and shots fired during each half-day hunt (n = 133) to evaluate hunt quality before and after the field trial. Bobwhite survival on Dixie was similar (P>0.05) during the two weeks prior to (0.89, SE = 0.026), during (0.93, SE = 0.023), and after (0.92, SE = 0.026) the field trial for the two years combined, as were seasonal survival curves between the two study sites for both years monitored. No differences (P>0.05) were observed in the number of coveys seen per half day hunt before (X = 11.78, SE = 0.39) compared to after (X = 12.35, SE = 0.44), covey rises shot before (X = 6.89, SE = 0.28) and after (X = 7.75, SE = 0.37), or number of shots fired before (X = 23.5, SE = 1.19) versus after (X =24.11 SE = 1.26) the field trial. We were unable to detect any evidence that the type of disturbance generated by this field trial had any effect on either bobwhite survival or post trial hunting quality on our study area.
Keywords: colinus virginianus; northern bobwhite; field trial; hunting; radio-telemetry; survival; bird dogs